![y=(7)/(3)x+6\text{ \& y=-}(3)/(7)x+4](https://img.qammunity.org/2023/formulas/mathematics/college/5ol84ud9zse3b3gp56p316xnwbpjx0i6is.png)
One of the criteria for lines being perpendicular is the fact that the slope of the function in a perpendicular line is the inverse of the slope of the first times -1.
And as you can see m (being the slope of the first equation) is the inverse of the second equiation:
![m=(7)/(3),m_1=-(1)/(m)](https://img.qammunity.org/2023/formulas/mathematics/college/272cri8ngfafsww7x5pw4fi3mdbhcgqjdw.png)
![-(1)/(m)=-(1)/((7)/(3))=-(3)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/ewidhefnhkojsqalt16iefg1c2ntqnezgt.png)
Therefore line 1 is perpendicular to line 2.